Perbedaan Sifat Fisik, Kimia dan Sensoris Tepung Umbi Suweg (Amorphophallus campamulatus BI) pada Fase Dorman dan Vegetatif - Umar Hafidz Asy’ari Hasbullah; Rini Umiyati (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
This study aims to determine ofdifferences in physical, chemical and sensory properties of suweg flour from the dormant and vegetative phases. Physical parameters include yield, edible portion, bulk density, brightness, particle size index, water absorption index and water solubility index. Chemical parameters include the moisture, ash, fat, protein, carbohydrates, starches and sugars reduction. Sensory parameters include hedonic test of color and aroma as well as descriptive test of color and aroma. The results showed that the physical characteristics of flour suweg dormant phase and vegetative phase significantly different at all parameters. Yield, edible portion, bulk density, brightness, particle size index of dorman phase higher than vegetative phase. Chemical characteristics from dormant phase and vegetative phase were significantly different at all parameters, except fat and carbohydrate. Starch contain in dorman phase higher than vegetative phase. But in contrast to the sugar reduction contain. Panellists assess the suweg flour produced from the vegetative phase has a more brown color and smells stronger than the dormant phase so it is less preferred color and aroma. Suweg flour should be selected from the dormant phase. Utilization of flour suweg is recommended for products such as cookies and biscuits that can be grown ingredients to cover the presence of brown and off flavor.